Palatalization in Romance: an investigation of the sound change in French and Spanish - Fielding, Steven (My University, 2010)
Abstract This thesis discusses and compares the change of velar stops into palatoalveolar affricates, a process termed velar palatalization, in the Romance languages French and Spanish. Firstly, velar palatalization will be defined and several explanations offered by other theorists will be examined. Evidence taken from these two languages, as well as their ancestor Proto-Romance, will be used to illustrate the process of velar palatalization. The question of how the process took place in both these languages will then be discussed. The voiceless velars will be examined first, followed by the voiced velars in Spanish and French, respectively. The voicing asymmetry noted will be discussed, with an explanation offered. Finally the unusual case of the velars palatalizing before the /a/ in French, which is normally dealt with as a separate change will be discussed and shown to be a case of velar palatalization.